Monsoon flood plain fishery and traditional fishing methods in Thrissur district, Kerala - Shaji CP & KP Laladhas (Indian Journal of Traditional Knowledge, 2013)
The breeding migration of the freshwater fishes is known locally as Oothayilakkom or Ootha. A study has been conducted during 2010 to study the fishery and fishing gears during Ootha. The traditional fishing gears, its fabrication and operation in Thrissur district were studied. Adichil, Chaattom, Nathoodu are gears unique to the study area. The impacts Ootha fishery on the sustainability of the fish resources and eco-friendliness of these gears were evaluated.